Isotemporal substitution of physical activity patterns and sitting time with obesity indicators among workers in São Paulo - Diego Sales; Gerson Ferrari; João Pedro da Silva Junior; Raiany Rosa Bergamo; Pedro Paulo de Oliveira Moda; Amauri dos Santos; Mauricio dos Santos; Victor Matsudo (Scientific Reports)
Abstract This study aimed to evaluate the association between substituting 10, 30, and 60 min/day of physical activity and sitting time with obesity indicators among workers. It is a cross-sectional study involving 394 adults (76.6% women) from São Paulo, Brazil. Physical activity and sitting time (min/day) were measured using the short version of the International Physical Activity Questionnaire (IPAQ) to determine physical activity levels. Obesity indicators included body mass index (BMI; kg/m²), waist circumference (cm), and body fat (kg). Isotemporal substitution models were analyzed using multivariate linear regression, adjusted for sociodemographic variables. Participants reported median values of 150.0 min/day (IQR: 60.0–360.0) for walking and 445.7 min/day (IQR: 317.1–565.7) for sitting time. The median values for BMI, waist circumference, and body fat were 27.1 kg/m², 91.0 cm, and 23.5 kg, respectively. Substituting 10 min/day of sitting time for 10 min/day of walking was associated with waist circumference (β: -0.216: 95% CI: -0.041; -0.007). In addition, substituting 60 min/day of sitting time for moderate physical activity (β -0.206; 95% CI: -0.123; -0.008) was negatively associated with body fat. The equivalent substitution of different periods of sitting time for more active behaviors was favorably associated with obesity indicators. These findings suggest that lifestyle interventions based on replacing sitting time with physical activity can reduce the obesity epidemic in adults.